Determinants of HIV testing uptake among adolescent girls and young women in mainland Tanzania: A stratified analysis of the 2016/17 and 2022/2023 national surveys - Deogratius W. Kinoko; Anthony C. Kavindi; Paschal Yuda; Jovin R. Tibenderana; Ahmed Y. Nyaki; Sia E. Msuya; Michael J. Mahande (PLoS ONE, 2026)
Background Adolescent girls and young women (AGYW) are disproportionately vulnerable to HIV. Despite expanded HIV testing services (HTS), the majority of AGYW remain unaware of their HIV status. This study aimed to assess determinants of HIV testing uptake among AGYW in mainland Tanzania before and after stratifying by age group (15–19 and 20–24 years) using data from two national surveys conducted over time. Methods The data from the Tanzania HIV Impact Surveys (2016/17 and 2022/23), collected using multi-stage stratified sampling, were analyzed on 12,714 adolescent girls and young women. Data analysis was performed using STATA version 17. Weighted Modified Poisson regression models with robust standard error were fitted to identify factors associated with HIV testing uptake before and after stratifying by age group (15–19 and 20–24 years). Results were presented as adjusted prevalence ratio (APR) with a 95% confidence interval. Results HIV testing uptake among adolescents remained stable at 40% in both the 2016/17 and 2022/23 surveys, while it increased among young women from 86% to 90% over the same period. Several factors were consistently associated with a higher prevalence of HIV testing uptake in both groups. Being in a union was more strongly associated with testing among adolescents (aPR = 1.52, 95% CI: 1.38–1.68) compared with young adults (aPR = 1.12, 95% CI: 1.07–1.17). Similarly, having secondary or higher education was associated with increased testing among adolescents (aPR = 1.22, 95% CI: 1.04–1.43) and young adults (aPR = 1.15, 95% CI: 1.06–1.25). A history of sexually transmitted infections (STIs) was also strongly associated with HIV testing uptake, particularly among adolescents (aPR = 1.53, 95% CI: 1.41–1.64), compared with young adults (aPR = 1.12, 95% CI: 1.09–1.15). Conclusions HIV testing uptake among AGYW in Tanzania has improved over time, with significant disparities between adolescents and young women. These findings highlight the need for age-specific strategies, intensifying adolescent-focused interventions while sustaining efforts among young women and reinforcing integrated reproductive health and HIV services.